PC.84 Withdrawal from "therapeutic" opiate during the neonatal period: an increasing problem?. (9th June 2014) - Johnson, K; Balain, M
Abstract : Background: There are well developed services for pregnant substance users maintained on opiate replacement therapies (ORT) both nationally and locally. Recently the problem of addiction to prescription drugs has been highlighted by the Home Affairs Select Committee report 1 and has received national media attention. Locally an increase in pregnant women addicted to such prescription drugs, particularly opiates, has been observed. Whilst ORT are prescription medications, they are distinct in some ways from opiates prescribed for non replacement therapy. Such opiates are referred to in this report as "therapeutic" opiates. Methods: Cases of infants born to mothers using "therapeutic" opiates over the last 2 years were reviewed. A literature review was performed looking specifically at the common substances used during pregnancy in such situations. Results: 22 women delivered 23 infants over the 2 year period. The most commonly prescribed substances were codeine, oxycodone and buprenorphine patches, prescribed mainly for chronic pain. All infants were admitted to the neonatal service for observation/treatment of Neonatal Abstinence Syndrome Very few women had accessed the local multi disciplinary antenatal clinic for drug using women and antenatal communication and planning was poor. Conclusions: The use of "therapeutic" opiates during pregnancy is not uncommon Women using "therapeutic" opiates are not accessing specialist local services, probably as they do not see themselves/are not seen as "addicts" in the classic sense of the word. There is clearly a need for improved services for this group of pregnant women. Reference: House of Commons Home Affairs Committee. Drugs: new psychoactive substances and prescription drugs. Twelfth Report of Session 2013-14. 17/12/2013